Factors affecting students’ participation and communication delivery in cybernated storytelling - Mohamed Rosli, Roziana; Idrus, Faizah; Anuar, Siti Zubaidah (Everant, 2016)
Storytelling is carried out as one of classroom activities to encourage students’ participation especially in improving English proficiency as well as communication delivery to language students. It is commonly recognized as a teaching technique to many educators because it engages students in learning. Nevertheless, little attention has been paid to how storytelling that is carried out is placed in the cyber world and then shared in social media can enhance students’ language skills. In this study, the term ‘cybernated storytelling’ is introduced. The word ‘cybernated’ is coined from the word cyber, which means a computer-generated setting in the internet environment. For this qualitative study, thirty five students were selected from a high school in Malaysia. The students had to produce a storytelling video and upload it in the internet. In the process of producing it, they were expected to communicate orally in face to face meetings and in writing using WhatsApp and Facebook platforms. The students were interviewed for data collection. Findings in this study show that there are eight factors that affect students’ participation and communication delivery in Cybernated Storytelling. Hence, the study implies that cybernated storytelling is meaningful and relevant in language courses that involve the present y generation and the future z generation